The Risk of Disease Progression in Peripheral Arterial Disease is Higher than Expected: A Meta-Analysis of Mortality and Disease Progression in Peripheral Arterial Disease. Issue 3 (March 2016) - Sigvant, B.; Lundin, F.; Wahlberg, E.
Abstract : Objective: Peripheral arterial disease (PAD) afflicts up to 20% of older people and is associated with a high risk of cardiovascular (CV) morbidity, but a rather low risk of progression of leg symptoms. These risk estimations are largely taken from cohort studies performed 20 years ago. To test the validity of this, available data were systematically reviewed and attempts were made to perform meta-analyses of CV risk and disease progression. Methods: A database literature search was conducted of the period 1990–2015 using related subject headings. Inclusion criteria were cohort studies for PAD, sample size >100 subjects, follow up time ≥1 year, and studies presenting endpoints covering mortality and/or CV events. Analyses were performed for a reference population, as well as groups with asymptomatic PAD (APAD), symptomatic PAD, and subjects with ankle brachial index <0.9. Results: Of 354 identified articles, 35 were eligible for systematic review. Sample size varied between 109 and 16, 440 subjects. Mean age in the cohorts ranged from 56 to 81 years (SD 10.8) and mean follow up was 6.3 years (range 1–13). Most included patients with symptomatic PAD had IC (91%). Symptomatic PAD subjects had higher 5 year cumulative CV mortality than the reference population, 13% versus 5%. During follow up, approximately 7% of APAD patients progressed to IC, and 21% of IC patients were diagnosed as having critical limb ischemia, with 4–27% undergoing amputations. Conclusion: The risk to the limb is underestimated in PAD patients, whereas the CV related morbidity is more moderate than stated in the guidelines. The latter observation is especially valid for IC patients. These findings should be considered when evaluating patients for treatment.